2021
DOI: 10.3390/jcm10194490
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Transmission of the Human Corneal Layers

Abstract: We have assessed the spectral transmittance of the different layers of the human cornea in the ultraviolet (UV), visible, and near-infrared (IR) spectral ranges. Seventy-four corneal sample donors were included in the study. Firstly, the corneal transmittance was measured using a spectrophotometer. Then, all samples were fixed for histopathological analysis, which allowed us to measure the thickness of each corneal layer. Finally, the absorption coefficients of the corneal layers were computed by a linear mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…At longer wavelengths, an almost full transmittance is observed for all the formulations. Thus, the results presented in Figure 3 are comparable to the previously described experimental results by Botettner and Wolter for a native cornea [ 46 ] and those estimated by Peris-Martinez et al [ 47 ], where it can be observed that there is a quick increment in the light transmitted between 300 and 500 nm (reaching around 70%) and, from there, a transmittance increase up to 98%.…”
Section: Resultssupporting
confidence: 90%
“…At longer wavelengths, an almost full transmittance is observed for all the formulations. Thus, the results presented in Figure 3 are comparable to the previously described experimental results by Botettner and Wolter for a native cornea [ 46 ] and those estimated by Peris-Martinez et al [ 47 ], where it can be observed that there is a quick increment in the light transmitted between 300 and 500 nm (reaching around 70%) and, from there, a transmittance increase up to 98%.…”
Section: Resultssupporting
confidence: 90%
“…The light transmittance in the visible region of the short-chain gellan gum represents the transparency of the material and was as high as 89% to 92%, which is close to that of the human corneal stroma. 58,59 Moreover, we hope that the hydrogel can stay on the ocular surface for enough time and degrade slowly, so that Rb-BMSCs can be released slowly onto the ocular surface to acquire satisfactory therapeutic outcomes. The in vitro cell release rate of the short-chain gellan gum was (61.02 6 4.00) % on day 7 which was quite satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The cornea is the main route for drug absorption after topical instillation, often referred to as a static (anatomical) barrier ( Figure 1 B). It is a transparent, highly specialized, avascular structure comprising six layers: the corneal epithelium, Bowman’s layer, stroma, Dua’s layer, Descemet’s membrane, and endothelium [ 59 , 60 ]. Among these, the epithelium, the stroma, and the endothelium have a primary role in the drug/nanocarrier transport.…”
Section: Eye Anatomy Barriers and Routes In Ocular Drug Deliverymentioning
confidence: 99%